Bohaterowie drugiego planu – o postaciach służących w operze - Sokalska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The article is devoted to the characters of servants in opera and their two radically different variants: a clever servant and a nursemaid. The first variant, rooted in the ancient tradition, becomes more independent with time, and these characters become fully-fledged and sometimes even turn into main characters (e.g. Figaro or Leporello.) The other variant is rooted in the Baroque, when nursemaids were treated, similarly to clever servants, as comic characters. The evolution of the character of a nursemaid in opera turns towards realism, fabulousness and highlighting archetypal features, which can be seen in the examples taken mainly from the Russian operatic tradition. Both types of servants in opera show that despite their socially secondary meaning, these characters serve important functions and become key for the interpretation of a particular scene as a whole.